Zimbabwe’s fast track land reform programme and its impact on food security in Southern African Development Community: a case of Zimbabwe, South Africa and Namibia - Chiwundura, B. K. (BUSE, 2023)
This research study aimed to investigate the “Zimbabwe’s Fast Track Land Reform Programme and its impact on Food Security in Southern African Development Community, A Case of Zimbabwe, South Africa and Namibia”. The research study aimed to carry out this investigation by looking into four main objectives which were firstly, to assess the impact of Zimbabwe's land reform policies on agricultural productivity and food security indicators, such as crop yields, food availability, and dietary diversity, within Zimbabwe itself, to examine the implications of Zimbabwe's land redistribution on regional food supply chains and trade dynamics within the Southern African Development Community (SADC), with a focus on potential disruptions and spillover effects on neighboring countries' food security, to investigate the socio-economic and political factors influencing the implementation and outcomes of land reform policies in Zimbabwe, South Africa, and Namibia, including land tenure systems, governance structures, and historical contexts and then lastly, to analyze the role of external actors, such as international donors, regional organizations, and foreign investors, in shaping land reform processes and their impacts on food security within the SADC region. Mixed methods research methodology was employed and the researcher used a combination of pragmatism and positivism research philosophies. The researcher used a sample size of 30 respondents and they were selected using purposive sampling technique. Questionnaires, Focus Group Discussions, Interview guides as well as observation guides were used as research instruments for the study. Quantitative data analysis was carried out using SPSS whilst for qualitative data, thematic analysis was utilized.
Keywords: Track Land Reform Programme; Food Security